A Cost-Benefit Framework for the Assessment of Non-Tariff Measures in Agro-Food Trade - van Tongeren, Frank (OECD Food, Agriculture and Fisheries Papers, 2009)
This report develops a conceptual framework for the assessment of costs and benefits associated with non-tariff measures that allows an evidence-based comparative assessment of alternative regulatory approaches